The role of c-MYC expression in the diagnostic and clinical confirmation of radiation-induced angiosarcoma - Jovanović, Luka; Filipović, Predrag; Dedović Stojaković, Jelena; Milovanović, Zorka; Labudović Borović, Milica; Tanasijević, Jasminka; Patrašinović, Predrag; Marinković, Tamara; Plešinac Karapandžić, Vesna (Vojnosanitetski pregled, 2022)
Introduction. Angiosarcomas (ASs) arising from vascular tissue, account for 3.3% of all sarcomas and have a poor prognosis. Radiation-induced AS is a rare late complication of radiotherapy (RT) treatment and is characterized by a gene expression profile such as amplification of the MYC oncogene, by which we can distinguish primary from secondary induced tumor. Case report. For a 77-year-old female patient with early-stage endometrial adenocarcinoma, a radical hysterectomy with bilateral salpingo-oophorectomy was initially done. According to pathological risk factors, the postoperative external beam conformal RT (CRT) of the pelvis was administered with concomitant brachytherapy. Six years after the treatment, on the anterior abdominal wall, in the region of the postoperative irradiation field and surgical scar, an infiltrative AS of the skin and subcutaneous adipose tissue was histologically confirmed. The patient received six cycles of mono-adriamycin chemotherapy with verified partial regression. Additional immunohistochemical analysis (IHC) of c-MYC, Ki67, and CD34 expression showed a high proliferative index (Ki67 around 60%) and c-MYC positivity indicating the molecular pattern of radiation-induced AS. Furthermore, the high proliferative index could explain the positive response to chemotherapy. Conclusion. The novel postoperative RT techniques provide better survival and local control in risk-endometrial cancer groups with a decrease in irradiation complications. These patients with longer survival are at a higher risk of developing radiation-induced tumors as late side-effects of RT. When assessing the probability of radiation-induced AS, IHC analysis of c-MYC expression could distinguish secondary from other AS if Cahan’s criteria are fulfilled.